2022
DOI: 10.4102/sajce.v12i1.967
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of reception class teachers’ pedagogical approaches in delivering pre-primary curriculum – Evidence from practice

Abstract: Background: This report is part of a study commissioned to provide evidence to inform quality improvements, and the rolling out of the public reception class programme (RCP) to all public primary schools in Botswana by 2020. The study adopted the Discrepancy Evaluation Model (DEM) as a theoretical framework.Aim: One of the specific objectives of the study was to determine the effectiveness of the programme in terms of the RCP curriculum coverage and the teachers' effectiveness in delivering the curriculum. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Although it is clearly written in the curriculum that teachers should take the initiative to plan for children at a level which is developmentally appropriate, some teachers were aiming at achieving learning outcomes and pitching the indicators at higher levels. Gaotlhobogwe et al (2022) reported that because of pressure from parents and supervisors, teachers were pitching the level of the RCP syllabus coverage higher than the expected level of 4 -5 year which confirms that the teachers were influenced by the culture and society in their analysis and interpretation of the curriculum. Bassok et al (2016) reported that the current perception is to prepare children so that they can be easily adjusted in the primary school which is mainly done by giving focus on basic knowledge of letters and numbers.…”
Section: Discussion Of the Findings Skills Developmental Levels In Th...mentioning
confidence: 88%
See 1 more Smart Citation
“…Although it is clearly written in the curriculum that teachers should take the initiative to plan for children at a level which is developmentally appropriate, some teachers were aiming at achieving learning outcomes and pitching the indicators at higher levels. Gaotlhobogwe et al (2022) reported that because of pressure from parents and supervisors, teachers were pitching the level of the RCP syllabus coverage higher than the expected level of 4 -5 year which confirms that the teachers were influenced by the culture and society in their analysis and interpretation of the curriculum. Bassok et al (2016) reported that the current perception is to prepare children so that they can be easily adjusted in the primary school which is mainly done by giving focus on basic knowledge of letters and numbers.…”
Section: Discussion Of the Findings Skills Developmental Levels In Th...mentioning
confidence: 88%
“…In the Botswana context, a pre-primary curriculum was developed by the Ministry of Basic From the inception of the piloting, there were a mixed feelings among reception class teachers on the interpretation of the pre-primary curriculum. A study by Gaotlhobogwe et al (2022) on the evaluation of the pre-primary curriculum reported that some teachers focused on the learning outcomes prescribed in the pre-primary curriculum and did not follow the developmentally appropriate approaches to promote children's progress. This implies that curriculum has different levels of skills development and teachers were interpreting them differently.…”
Section: Introductionmentioning
confidence: 99%
“…e quality of air has farreaching significance and influence on human survival and development, food, clothing, shelter and transportation, and harmonious coexistence of nature. If we can accurately predict the level of air quality in an area, we can do a good job of protection and relevant countermeasures in advance and minimize the harm and adverse impact of air quality deterioration on life [12]. 730 air quality grade data pieces of Taiyuan city from April 1, 2019, to March 31, 2021, are selected and modeled by Markov model.…”
Section: Literature Reviewmentioning
confidence: 99%